POLA INTERAKSI GURU DAN SISWA DALAM MENCIPTAKAN SUASANA BELAJAR YANG EFEKTIF DI SDN KLAMPOK 02 SINGOSARI - Anis Khoirotun Nikmah; Mohammad Afifulloh; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
Education is an aspect that has a very basic role in shaping the personality of a bright young generation in the future. It is through education that all human beings can learn. Organizing a learning environment in the classroom that attracts interest and supports students in learning is closely related to the state of the physical classroom environment, room arrangements, student management and utilization of learning resources, classroom displays, and so on. Classrooms must be clean, seating arranged in such a way that children can carry out learning activities freely. The purpose of this study is to explain the teacher-student interaction model in creativity an effective learning atmosphere. To achieve this goal, the researcher conducted a qualitative research type. The data collection procedure was carried out using observation method, That is, verbally asking and responding to sources of information chosen by researchers in direct observation, interviews and certain data collection methods to find phenomena in research activities carried out systematically, and so on. A documentary way to get data. , Notes, agenda, etc.Kata kunci: Pola Interaksi, Guru dan Siswa, Pembelajaran Efektif